Modeling of the Excise Taxation Influence on Components of Human Potential - Londar, Serhii; Kozarezenko, Liudmila (Oeconomia Copernicana, 2015)
The purpose of the research is analysis of a model of influence of excise tax rate increase for tobacco products in Ukraine on financial indices of state funds, prevalence of tobacco smoking, and indices of society health. Due to the results of research, the author determined the opportunities of the excise tax for tobacco smoking prevalence regulation in Ukraine. The dynamics of changes of specific and ad valorem rates of the excise tax and the dynamics of its contribution to the revenues of the State Budget of Ukraine were analyzed. The author estimated the changes of tobacco smoking prevalence in Ukraine on the basis of an adapted imitation model under conditions of increase of excise tax rates to the level of rates of the European Union countries. The research shows the excise tax is an effective financial regulator of tobacco smoking prevalence in Ukraine and it influences a population health condition. Increase of the excise tax rates causes reduction of amounts of tobacco product consumption and decrease of the share of smoking adults. Gradual increase of the Ukrainian rates to the level of the EU before 2018 may allow pulling from 1.0 to 1.9 million of people through premature death. Aside from a positive social effect of health enhancement, increase of the share of excise tax within a structure of a retail price of tobacco products will positively influence the growth of tax incomings to the State Budget. Consequently, under the Ukrainian contemporary economic environment the excise tax is an effective financial regulator of tobacco smoking prevalence.